2009
DOI: 10.5216/ree.v11i4.5197
|View full text |Cite
|
Sign up to set email alerts
|

Vivências e sentimentos do cuidador familiar do paciente oncológico em cuidados paliativos

Abstract: O câncer e seu tratamento exercem grande influência sobre os pacientes e seus familiares. Esse estudo buscou conhecer a vivência e sentimentos do cuidador familiar do paciente oncológico em cuidados paliativos. Trata-se de pesquisa descritiva com abordagem qualitativa, na qual participaram seis cuidadores familiares de portadores de câncer em cuidados paliativos, vinculados ao Sistema de Internação Domiciliar de Londrina/Paraná. Os dados foram coletados no período de junho a agosto de 2008, por meio da entrevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
34

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 13 publications
0
28
0
34
Order By: Relevance
“…Family is an important core in the formation of the beliefs, values, and knowledge of the individual, and in general the consequences of the illness are experienced by the whole family. Therefore, without a support network, the patient under palliative care undergoes excessive suffering, not only due to the disease itself, but also due to the absence of important people that may support their care at the end of life (16) . The study revealed that nearly half the patients presented comorbidities, but only a quarter of them presented a high comorbidity index, indicating a low risk of associated death.…”
Section: Discussionmentioning
confidence: 99%
“…Family is an important core in the formation of the beliefs, values, and knowledge of the individual, and in general the consequences of the illness are experienced by the whole family. Therefore, without a support network, the patient under palliative care undergoes excessive suffering, not only due to the disease itself, but also due to the absence of important people that may support their care at the end of life (16) . The study revealed that nearly half the patients presented comorbidities, but only a quarter of them presented a high comorbidity index, indicating a low risk of associated death.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, essa relação pode causar sentimentos de opressão, pesar, tristeza, entre outros. Quando se trata de um familiar, o vínculo pode tornar-se maior e a relação de compaixão e solidariedade faz com que o cuidador esteja sujeito a esse misto de sentimentos diante da situação 13 .…”
Section: Resultados E Discussõesunclassified
“…Isto porque coexistem na situação de cuidado sentimentos ambivalentes que se relacionam tanto com a sobrecarga decorrente das tarefas, quanto com sentimentos de amor, empatia e gratidão 14,18 . Outro aspecto identificado neste estudo e confirmado pela literatura é que em casos de pacientes terminais, o cuidador acaba se aproximando mais do idoso e os vínculos são estreitados, aumentando sentimentos de compaixão e solidariedade 19 .…”
Section: Discussionunclassified